Presentation: Using improvisational skills in teaching music and drama - Karjalainen-Väkevä, Mirja (BUKS - Tidsskrift for Børne- & Ungdomskultur, 2016)
How can techniques adapted from improvisation in music and drama promote creative teaching and learning? Firstly, I discuss why improvisation is important in teaching. I present aspects of improvisation relevant to both dramatic and musical improvisation, and reflect on how these skills could also serve teaching, especially in the subjects of drama and music.